2013
DOI: 10.1007/s00784-013-0937-z
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein-3/γ-catenin and E-cadherin/ß-catenin differential expression in oral leukoplakia and squamous cell carcinoma

Abstract: The observed alterations of their expression suggest a role of Dsg3 and γ-catenin (additionally to E-cadherin/β-catenin) as biomarkers of malignant transformation risk of oral dysplasia and the biological behavior (aggressiveness) of oral cancer, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Besides, Kyrodimou et al (2013) and Gómez-Morales et al (2013) report that DSG3 is a marker for poorly differentiated OSCC and also for squamous differentiation in non-small-cell carcinomas. Consistent with these results, we observe that lose of DSG3 expression is associated with poor differentiation in ESCC, but not with lymphatic metastases and depth of tumor invasion, suggesting that the reduction of DSG3 expression is associated with loss of the ability of adhesion, as previously reported (Hartlieb et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Kyrodimou et al (2013) and Gómez-Morales et al (2013) report that DSG3 is a marker for poorly differentiated OSCC and also for squamous differentiation in non-small-cell carcinomas. Consistent with these results, we observe that lose of DSG3 expression is associated with poor differentiation in ESCC, but not with lymphatic metastases and depth of tumor invasion, suggesting that the reduction of DSG3 expression is associated with loss of the ability of adhesion, as previously reported (Hartlieb et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This reveals that E-cadherin might have a close association with the pathological features and biological behavior of tumors. E-cadherin not only plays an important role in cancer pathogenesis and metastasis, but is also greatly involved in the development of precancerous lesions, indicated by the fact that the abnormal expression of E-cadherin has been observed in oral leukoplakia and cervical intraepithelial neoplasia (15,16). Therefore, it is suggested that E-cadherin might be a suitable indicator for the early detection, diagnosis and prevention of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…After reading the titles and abstracts, 54 studies were considered potentially eligible and their full text was read by three reviewers. Seventeen articles met all inclusion criteria and were selected for this systematic review (5,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The selected articles were observational studies published between 2007 and 2018, all of them in English.…”
Section: Resultsmentioning
confidence: 99%
“…Anura et al (25) and Sharada et al (33) also evaluated tissue samples of oral submucosal fibrosis. Twelve studies included samples of oral squamous cell carcinoma (OSCC) for biomarker analysis, totaling 426 cases analyzed (5,18,21,23,24,(26)(27)(28)(31)(32)(33). Tissue (F) Cytokeratin-13 loss was found to be an independent diagnostic marker for high-grade dysplasia.…”
Section: Resultsmentioning
confidence: 99%